CRISPR/Cas13-Based Platforms for a Potential Next-Generation Diagnosis of Colorectal Cancer through Exosomes Micro-RNA Detection: A Review - Benjamín Durán-Vinet; Karla Araya-Castro; CALDERON GIADROSIC, JUAN FRANCISCO; Luis Vergara; Helga Weber; Javier Retamales; ARAYA CASTRO, PAULINA ANDREA; Pamela Leal-Rojas (My University, 2021)
Colorectal cancer (CRC) is the third most prevalent cancer with the second highest mortality rate worldwide. CRC is a heterogenous disease with multiple risk factors associated, including obesity, smoking, and use of alcohol. Of total CRC cases, 60% are diagnosed in late stages, where survival can drop to about 10%. CRC screening programs are based primarily on colonoscopy, yet this approach is invasive and has low patient adherence. Therefore, there is a strong incentive for developing molecular-based methods that are minimally invasive and have higher patient adherence. Recent reports have highlighted the importance of extracellular vesicles (EVs), specifically exosomes, as intercellular communication vehicles with a broad cargo, including micro-RNAs (miRNAs). These have been syndicated as robust candidates for diagnosis, primarily for their known activities in cancer cells, including immunoevasion, tumor progression, and angiogenesis, whereas miRNAs are dysregulated by cancer cells and delivered by cancer-derived exosomes (CEx). Quantitative polymerase chain reaction (qPCR) has shown good results detecting specific cancer-derived exosome micro-RNAs (CEx-miRNAs) associated with CRC, but qPCR also has several challenges, including portability and sensitivity/specificity issues regarding experiment design and sample quality. CRISPR/Cas-based platforms have been presented as cost-effective, ultrasensitive, specific, and robust clinical detection tools in the presence of potential inhibitors and capable of delivering quantitative and qualitative real-time data for enhanced decision-making to healthcare teams. Thereby, CRISPR/Cas13-based technologies have become a potential strategy for early CRC diagnosis detecting CEx-miRNAs. Moreover, CRISPR/Cas13-based platforms’ ease of use, scalability, and portability also showcase them as a potential point-of-care (POC) technology for CRC early diagnosis. This study presents two potential CRISPR/Cas13-based methodologies with a proposed panel consisting of four CEx-miRNAs, including miR-126, miR-1290, miR-23a, and miR-940, to streamline novel applications which may deliver a potential early diagnosis and prognosis of CRC.
Keywords: crc; mirna; exosomes; crispr; cas systems; molecular diagnosis; microrna; angiogenesis; cancer cell; cancer prognosis; cancer survival; colorectal cancer; crispr-cas9 system; decision making; exosome; human; intercellular signaling; molecular diagnosis; nonhuman; polymerase chain reaction; qualitative analysis; quantitative analysis; review; risk factor; sensitivity and specificity; tumor growth